Comparative hydrological analysis stations on the boundary River Sotla/Sutla (Slovenia–Croatia) - Bonacci, Ognjen (Acta hydrotechnica, 2025)
This study examines hydrological processes at the Zelenjak (1958–2023) and Rakovec (1926–2022) stations on the Sotla/Sutla River, analyzed on an annual time scale. The analysis includes time series of annual minimum and maximum mean daily flows and mean annual flows. Additionally, data on annual precipitation and mean annual temperatures measured at the climatological station Bizeljsko in the period 1951 to 2024 were used to calculate annual runoff coefficients at the Zelenjak and Rakovec stations. The New Drought Index (NDI) was calculated using precipitation and air temperature data measured at the Bizeljsko climatological station. All analyses indicated a strong variability of the analyzed parameters over the available data period. A clear downward trend in mean annual flows is observed. In the recent period, from 2000 onward, there has been a sharp increase in mean annual air temperatures and a decline in all other analyzed hydrological and climatological parameters. Particularly concerning is the notable rise in the frequency and intensity of droughts in the 2000–2024 period. The causes of these trends could not be reliably determined through an analysis conducted on an annual time scale. It appears that natural factors, particularly the sharp rise in air temperatures, have played a significant role. However, it is important to emphasize that the natural characteristics of the Sotla/Sutla River basin have, to date, remained largely unaffected by human interventions. Furthermore, the insufficient accuracy in defining peak flows must be considered, as the rating curves used to define maximum flows may not have been reliable in certain periods.
Keywords: air temperature; climatological station Bizeljsko; flow; klimatološka postaja Bizeljsko; merilna postaja Rakovec; merilna postaja Zelenjak; padavine; precipitation; pretok; Rakovec gauging stations; reka Sotla; Sotla River; temperatura zraka; Zelenjak gauging stations